2022
DOI: 10.1093/jme/tjac101
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegypti (L.) and Anopheles stephensi Liston (Diptera: Culicidae) Susceptibility and Response to Different Experimental Formulations of a Sodium Ascorbate Toxic Sugar Bait

Abstract: Attractive toxic sugar baits (ATSBs) require target insects to locate, orient toward, and feed on an insecticidal sugar solution to control populations. Formulating these baits with different attractants and phagostimulants can increase their efficacy by causing insects to choose the ATSB over competing natural sugar sources, and to ingest more of the bait solution. We tested formulations of a 20% sodium ascorbate (SA) ATSB solution using different sugars, adenosine triphosphate (ATP), gallic acid, and six pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Yet, we observed multiple landings from both species. This could be attributed to the ratio of different volatiles in Lantana’s scent profile; benzaldehyde was also a major constituent in Lantana scent and has been hypothesized to attract mosquitoes when present in volatile blends 39 . In the scent profile of butterfly bush, ɑ -farnesene was a prominent volatile; its enantiomer β-farnesene has demonstrated a low degree of repellence in Ae.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Yet, we observed multiple landings from both species. This could be attributed to the ratio of different volatiles in Lantana’s scent profile; benzaldehyde was also a major constituent in Lantana scent and has been hypothesized to attract mosquitoes when present in volatile blends 39 . In the scent profile of butterfly bush, ɑ -farnesene was a prominent volatile; its enantiomer β-farnesene has demonstrated a low degree of repellence in Ae.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Yet, multiple landings were observed from both species in the present study. This could be attributed to the ratio of different volatiles in Lantana's scent profile; benzaldehyde was also a major constituent in Lantana scent and has been hypothesized to attract mosquitoes when present in volatile blends [46]. It has been shown that Ae.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%